The elusive West and the contest for empire, 1713-1763 - Mapp, Paul W. (UPCC book collections on Project MUSE. History., 2011)
This is a truly continental history in both its geographic and political scope. The book investigates 18th-century diplomacy involving North America and links geographic ignorance about the American West to Europeans' grand geopolitical designs.